THE EFFECT OF JOB ROTATION AND COMMUNICATION ON EMPLOYEE WORK PERFORMANCE AT THE COMMODITY FUTURES TRADING SUPERVISORY AGENCY - Dwi Risa Pusti; Enjang Sudarman; Bambang Nurakhim (Jurnal Manajemen Bisnis Dan Organisasi, 2026)
This study aims to determine the effect of job rotation and communication on employee performance at the commodity futures trading supervisory agency. The underlying phenomenon of this study is the discovery of employees with suboptimal levels of work performance. In this study, the author used quantitative research. The population in this study was 156 employees. In this study, the author used a sampling technique using the Slovin formula for 112 people. Data were collected using a closed questionnaire with a Likert scale, and analyzed using multiple linear regression with the help of the SPSS program version 20. The results of the study indicate that partially and simultaneously, the influence of job rotation and communication has a positive and significant effect on work performance. This study emphasizes the importance of being able to follow up with appropriate policies in order to be able to improve work performance optimally.